Effect of Quercetin supplementation on repeated-sprint performance, Xanthine oxidase activity, and inflammation - Abbey, E. L.; Walberg Rankin, J. (International Journal of Sport Nutrition and Exercise Metabolism, 2011)
Maintenance of repeated-sprint performance is a goal during team-sport competition such as soccer. Quercetin has been shown to be an adenosine-receptor antagonist and may reduce oxidative stress via inhibition of the enzyme xanthine oxidase (XO). The purpose of the study was to determine the effect of quercetin consumption on performance of repeated sprints and, secondarily, the XO and inflammatory-marker response induced by repeated-sprint exercise. Fifteen recreationally active, young adult men completed 2 repeated-sprint tests (RST), 12 × 30-m maximal-effort sprints (S1-S12), each after 1 wk supplementation with a placebo, a 6% carbohydrate commercial sports drink, or that drink with 500 mg of quercetin-3-glucoside, consumed twice a day (1,000 mg/d). Blood samples were collected before supplementation (B0), at baseline before each RST (B1), immediately after RST (B2), and 1 hr after RST (B3). Mean sprint time increased progressively and was significantly higher by S9 for both treatments (5.9%); however, there were no significant differences between treatments. Percent fatigue decrement (%FD) for placebo (3.8% ± 2.3%) was significantly less than with quercetin (5.1% ± 2.7%). Changes in blood XO, IL-6, and uric acid from B1 to B2 were +47%, +77%, and +25%, respectively, with no difference by treatment. In conclusion, repeated-sprint performance was not improved by quercetin supplementation and was worse than with placebo when expressed as %FD. Quercetin did not attenuate indicators of XO activity or IL-6, a marker of the inflammatory response after sprint exercise.